EFFECT OF 1,2-EPOXY-3[3-3[3,4-DIMETOXYI-PHENIL]-4H-1-BENZOPIRAN-4-ON] PROPANE (EPI) ON SIRTUIN-1 AND NUCLEAR FACTOR-κB EXPRESSION OF MAMMARY TUMORS INDUCED IN SPRAGUE DAWLEY RATS BY DMBA - Ayyub Harly Nurung; Sri Herwiyanti; Dewi Kartikawati Paramita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACT The main factors contribute to breast cancer development is the combination of exogenous and endogenous factors. Endogenous factors include both SIRT1 and NF-kB. Exogenous factor used in this research is 7.12 dimethylbenz(a)anthracene (DMBA). 1,2-epoxy-3[3- 3[3,4-dimetoxy-phenil]-4h-1-benzophiran-4-on] propane (EPI) is a derivative of isoflavone generate from clove leaf oil. To examine the effect of EPI on SIRT1 and NF-kB expression in DMBA-induced Sprague Dawley (SD) rats, and the correlation between SIRT1 and NFkB expressions. Tissue generated form 35 Sprague Dawley female rats aged 2 weeks old were used in this study. Those rats were divided into 7 groups (5 rats/group), namely normal control group; corn oil group; DMBA group; EPI treated groups with 1 mg/kgBW (EPI I), 2 mg/kgBW (EPI II), and 4 mg/kgBW (EPI III), respectively; and doxorubicin group. EPI and doxorubicin were administered from 1st until 15th week, while DMBA were administered from 3rd until 9th week. The paraffin block was prepared from all breast organ of the rats that terminated at the end of week 15th. Examination of SIRT1 and NF-kB expression was performed using light microscope at 400x magnifications, after immunohistochemistry (IHC) staining. Expression level of SIRT1 and NF-kB were analyzed using IHC-profiler plug-in in ImageJ software. SIRT1 and NF-kB expression in EPI treated groups were not significantly different with the one in Doxorubicin group, but lower than DMBA group (p=0.000). There was a positive correlation between SIRT1 and NF-kB expression (p=0.001; r=0.773) in EPI-treated group. EPI was able to prevent an increasing of SIRT1 and NF-kB expression in SD model breast cancer that induced with DMBA. There is a positive correlation between SIRT1 and NF-kB expression in EPI-treated SD rats that were induced by DMBA